CHEMISTRY SCIENCE REMOTE IN TEACHING INTERACTIVE FROM THE METHOD USE - Xamidov Sodiqjon; Hikmatova Hilola (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This in the article chemistry science from a distance teaching in the process one how many different interactive of the methods use This methods use through students free to thinking to teach and lessons interesting organize reach circle briefly information given.